2017
DOI: 10.1017/s0958344017000131
|View full text |Cite
|
Sign up to set email alerts
|

Dictionary form in decoding, encoding and retention: Further insights

Abstract: The aim of the paper is to investigate the role of dictionary form (paper versus electronic) in language reception, production and retention. The body of existing research does not give a clear answer as to which dictionary medium benefits users more. Divergent findings from many studies into the topic might stem from differences in research methodology (including the various tasks, participants and dictionaries used by different authors). Even a series of studies conducted by one researcher (Dziemianko, 2010,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
0
6
0
2
Order By: Relevance
“…However, studies comparing on-line to paper or book-based to electronic or on-line dictionaries have provided mixed results. Chen (2012) and Dziemianko (2011, 2012) did not find significant differences for vocabulary learning between the two types of dictionaries, but Dziemianko (2010, 2017) found on-line dictionaries were better for the learning of nouns, phrases, and collocations compared to book-based dictionaries. With regard to on-line dictionaries themselves, Liu and Lin (2011) and Alharbi (2016) found that learners acquired the meanings of words more quickly when accessed through a pop-up dictionary as opposed to a type-in dictionary.…”
Section: Background Researchmentioning
confidence: 92%
“…However, studies comparing on-line to paper or book-based to electronic or on-line dictionaries have provided mixed results. Chen (2012) and Dziemianko (2011, 2012) did not find significant differences for vocabulary learning between the two types of dictionaries, but Dziemianko (2010, 2017) found on-line dictionaries were better for the learning of nouns, phrases, and collocations compared to book-based dictionaries. With regard to on-line dictionaries themselves, Liu and Lin (2011) and Alharbi (2016) found that learners acquired the meanings of words more quickly when accessed through a pop-up dictionary as opposed to a type-in dictionary.…”
Section: Background Researchmentioning
confidence: 92%
“…Building on the wide recognition of dictionaries as tools for looking up unknown words for improving vocabulary knowledge (Nist & Olejnik, 1995;Gonzalez & Gonzales, 1999), or more broadly for vocabulary learning (Nation, 1989), the bulk of CALL research sought to understand the impact of online dictionaries on the learning (Collins, 2016;Wang, 2012) and retention of vocabulary (e.g. Chen, 2016;Dziemianko, 2010Dziemianko, , 2017Peters, 2007). Similarly, the use of online dictionaries in the form of glosses was investigated in reading (e.g., Abraham, 2008;Yanguas, 2009;Yun, 2011;Poole, 2012;Hu et al, 2014;Chen, 2014;Türk & Erçetin, 2014;Lee et al, 2017) and writing (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…McKeown testete die Effektivität der schülergerechten gegenüber den klassischen Definitionen mit Schülerinnen und Schülern im Alter zwischen zehn und elf Jahren. Since so many other aspects of the definitions were difficult, they depended on that first formulation and worked to make the language of the sentences and definitions match these early Dziemianko (2010Dziemianko ( , 2011Dziemianko ( , 2012Dziemianko ( , 2017…”
Section: Pop-up M (Sd)unclassified